2021
DOI: 10.1097/ruq.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Variability of Ultrasound Features Based on American College of Radiology Thyroid Imaging Reporting and Data System Lexicon in American College of Radiology Thyroid Imaging Reporting and Data System System

Abstract: The aim of this study is to evaluate the variability of selecting the ultrasound features used in American College of Radiology Thyroid Imaging Reporting and Data System (ACR-TIRADS) and in assigning the ACR-TIRADS level in a single center among radiologists and radiology residents. The study cohort consisted of 108 thyroid nodules in 102 patients who had definite cytology results after thyroid fine needle aspiration biopsy (Bethesda category II, VI) or surgery. Seven observers including 3 radiologists and 4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
2
Order By: Relevance
“…Based on our findings, interobserver agreement was insufficient for evaluation of nodule margins and moderate for microcalcifications, a clear difference compared to previous studies which found better agreement (19,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) using still images (Figure 2), while intraobserver variation was comparable (Figure 3). This is explained almost exclusively by the difference in observer-dependent interpretation of nodule characteristics; while microcalcification and taller-than-wide shape have clear definitions, this is less true for nodule margins.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Based on our findings, interobserver agreement was insufficient for evaluation of nodule margins and moderate for microcalcifications, a clear difference compared to previous studies which found better agreement (19,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) using still images (Figure 2), while intraobserver variation was comparable (Figure 3). This is explained almost exclusively by the difference in observer-dependent interpretation of nodule characteristics; while microcalcification and taller-than-wide shape have clear definitions, this is less true for nodule margins.…”
Section: Discussioncontrasting
confidence: 78%
“…Based on our findings, interobserver agreement was insufficient for the evaluation of nodule margins and moderate for microcalcifications, a clear difference compared to previous studies which found better agreement ( 19 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ) using still images ( Fig. 2 ), while intraobserver variation was comparable ( Fig.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Of the 951 articles identified via the database search, 35 met eligibility criteria (Figure 1). 18–52 We found that the inter‐rater reliability amongst independent reviewers for the abstract screening and full‐text review stages was 0.704 (95% CI: 0.628, 0.781) and 0.766 (95% CI: 0.630, 0.903), respectively.…”
Section: Resultsmentioning
confidence: 92%